Justification of the use of forest waste in the power industry as one of the components OF BIO-coal-water suspension fuel; Energy; Vol. 239 - Kuznetsov G. V. Geny Vladimirovich; Malyshev D. Yu. Dmitry Yurievich; Syrodoy S. V. Semen Vladimirovich; Gutareva N. Yu. Nadezhda Yurievna; Purin M. V. Mikhail Vladimirovich; Kostoreva Zh. A. Zhanna Andreevna (2022, 2022)
Title screen